A human nasal explant model to study Staphylococcus aureus biofilm in vitro. Issue 7 (12th February 2013) - Cantero, Daniel; Cooksley, Clare; Jardeleza, Camille; Bassiouni, Ahmed; Jones, Damien; Wormald, Peter‐John; Vreugde, Sarah
<x xml:space="preserve">Abstract</x> Background Staphylococcus aureus (S. aureus) biofilm has been associated with severe and recalcitrant cases of chronic rhinosinusitis (CRS). However, its role in the pathophysiology of this condition is not completely understood. This study aims to develop a sinonasal tissue explant model to analyze the interaction of S. aureus biofilm with the mucosa in vitro. Methods Sinonasal tissue samples from 5 control patients undergoing pituitary surgery were cultured with and without S. aureus biofilm in vitro. Confocal scanning laser microscopy (CSLM) using the Live/Dead BacLight stain and histology were performed on the tissue explants after 24 hours of biofilm challenge. Measurements of IL‐6, at both the messenger RNA (mRNA) level (using quantitative reverse‐transcriptase polymerase chain reaction [qRT‐PCR]) and the protein level (using enzyme‐linked immunosorbent assay [ELISA]), were undertaken to evaluate biofilm‐mucosa interaction. Results Viability of the explants after 24 hours was confirmed by CSLM and histology. Although light microscopy failed to identify S. aureus biofilms, its presence was confirmed in the biofilm‐challenged samples by CSLM. IL‐6 mRNA transcript levels were 4.9‐fold upregulated in biofilm‐treated tissue compared to controls (p = 0.0485). A similar trend was observed at the protein level (p = 0.0313). Conclusion The sinonasal tissue explant is a viable and functional model capable of analyzing direct biofilm‐mucosal interactions and can advance our understanding of the role played by S. aureus biofilm in sinus inflammation. Our model suggests that S. aureus biofilms in the initial phase of growth are not inert bystanders but elicit an immune response in the sinonasal mucosa.